2021
DOI: 10.3389/fpls.2021.721558
|View full text |Cite
|
Sign up to set email alerts
|

Genome-Wide Comparative Analysis of R2R3 MYB Gene Family in Populus and Salix and Identification of Male Flower Bud Development-Related Genes

Abstract: The MYB transcription factor (TF) family is one of the largest plant transcription factor gene family playing vital roles in plant growth and development, including defense, cell differentiation, secondary metabolism, and responses to biotic and abiotic stresses. As a model tree species of woody plants, in recent years, the identification and functional prediction of certain MYB family members in the poplar genome have been reported. However, to date, the characterization of the gene family in the genome of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 113 publications
(159 reference statements)
4
20
0
Order By: Relevance
“…In this research, we identified a total of 210 R2R3-MYB transcription factors (TFs) comprising an adjacent MYB repeat pair from the P. trichocarpa genome (v3.0) ( Table S1 ). These R2R3-MYB TFs were compared with those of four previously published papers ( Figure 1 ) [ 25 , 26 , 27 , 28 ]. The union set of all P. trichocarpa R2R3-MYB TFs reported previously in the four papers comprised 211 protein-coding genes, only one (Potri.015G143400.1) of which was not included in the 210 R2R3-MYB genes that we identified.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In this research, we identified a total of 210 R2R3-MYB transcription factors (TFs) comprising an adjacent MYB repeat pair from the P. trichocarpa genome (v3.0) ( Table S1 ). These R2R3-MYB TFs were compared with those of four previously published papers ( Figure 1 ) [ 25 , 26 , 27 , 28 ]. The union set of all P. trichocarpa R2R3-MYB TFs reported previously in the four papers comprised 211 protein-coding genes, only one (Potri.015G143400.1) of which was not included in the 210 R2R3-MYB genes that we identified.…”
Section: Resultsmentioning
confidence: 99%
“…Many studies have shown that whole-genome duplication (WGD) and fragment duplication events are important mechanisms by which the R2R3-MYB gene family has rapidly expanded during poplar genome evolution [ 28 ]. Chromosomal mapping analysis showed that 207 R2R3-MYB genes were unevenly distributed over 19 P. trichocarpa chromosomes, and most R2R3-MYB genes were concentrated on certain chromosomal regions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The primer sequences of the target gene are shown in Table 1 and the qRT-PCR procedure was the same as described above. The gene expression was analyzed using the 2 −ΔΔCt method [ 51 , 52 , 53 ].…”
Section: Methodsmentioning
confidence: 99%
“…Multiple lines of evidence have confirmed that the MIXTA genes, which belong to the ninth subgroup of the R2R3 MYB subfamily, play a significant role in regulating epidermal cells differentiation ( e.g ., Lau et al ., 2015; Wu et al ., 2018; Zhao et al ., 2020). As an example, AmMIXTA1 , the first MIXTA gene, discovered in an Antirrhinum majus mutant, is the key regulator triggering petal epidermal cells differentiation into conical cells (Zhou et al ., 2021; Brockington et al ., 2013; Ambawat et al ., 2013; Lau et al ., 2015; Du et al ., 2012; Jaffe et al ., 2007). In Artemisia annua, AaMIXTA1 , a homolog of AmMIXTA1 , overexpression results in a significant increase in glandular secretory trichomes (GSTs) (Shi et al ., 2018).…”
Section: Introductionmentioning
confidence: 99%